2015
DOI: 10.1371/journal.pone.0138942
|View full text |Cite
|
Sign up to set email alerts
|

Construction of an SSR and RAD-Marker Based Molecular Linkage Map of Vigna vexillata (L.) A. Rich

Abstract: Vigna vexillata (L.) A. Rich. (tuber cowpea) is an underutilized crop for consuming its tuber and mature seeds. Wild form of V. vexillata is a pan-tropical perennial herbaceous plant which has been used by local people as a food. Wild V. vexillata has also been considered as useful gene(s) source for V. unguiculata (cowpea), since it was reported to have various resistance gene(s) for insects and diseases of cowpea. To exploit the potential of V. vexillata, an SSR-based linkage map of V. vexillata was develope… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
16
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 53 publications
5
16
3
Order By: Relevance
“…In addition, Dachapak et al [4] reported that only 21.2% of 1,024 SSR markers screened in 6 accessions of V. vexillata from Asia, Africa, Australia and America were polymorphic. However, the percentage of amplifiable SSR markers in Marubodee et al [33] and Dachapak et al [4] (65.4% and 58.1%, respectively) was higher than in our study (36.6%). It is worth noting that almost all of the markers used by Marubodee et al [33] and Dachapak et al [4] were used in our study.…”
Section: Discussioncontrasting
confidence: 88%
See 3 more Smart Citations
“…In addition, Dachapak et al [4] reported that only 21.2% of 1,024 SSR markers screened in 6 accessions of V. vexillata from Asia, Africa, Australia and America were polymorphic. However, the percentage of amplifiable SSR markers in Marubodee et al [33] and Dachapak et al [4] (65.4% and 58.1%, respectively) was higher than in our study (36.6%). It is worth noting that almost all of the markers used by Marubodee et al [33] and Dachapak et al [4] were used in our study.…”
Section: Discussioncontrasting
confidence: 88%
“…However, the percentage of amplifiable SSR markers in Marubodee et al [33] and Dachapak et al [4] (65.4% and 58.1%, respectively) was higher than in our study (36.6%). It is worth noting that almost all of the markers used by Marubodee et al [33] and Dachapak et al [4] were used in our study. Nonetheless, these results indicate moderate transferability but low polymorphism of SSR markers from other Vigna species in V. vexillata .…”
Section: Discussioncontrasting
confidence: 88%
See 2 more Smart Citations
“…macrosperma Maréchal, Mascherpa & Stainier (JP235905: macro) were used in this study. V1 and V5 are known as salt-tolerant and susceptible accessions, respectively (Marubodee et al, 2015). All of the accessions were provided by the Genebank, National Agriculture and Food Research Organization, Tsukuba, Japan.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%